Fullerenols: Physicochemical properties and applications. (June 2016) - Semenov, K.N.; Charykov, N.A.; Postnov, V.N.; Sharoyko, V.V.; Vorotyntsev, I.V.; Galagudza, M.M.; Murin, I.V.
Abstract: Fullerenols may find the widest application in science and technology. This causes particular interest in developing available and simple methods for the synthesis of water-soluble polyhydroxylated fullerene derivatives on an industrial scale as well as investigating the physicochemical and biological properties and principles of their application. This study systematizes the current literature data on the synthesis, physicochemical properties, and application of polyhydroxylated fullerenes (fullerenols), a class of water-soluble fullerene derivatives. The experimental and theoretical data presented in this study provide a comprehensive overview of these substances and can be valuable to specialists in the fields of nanotechnology, nanomaterials, and nanobiomedicine.